Moralitas Agama dalam Krisis Lingkungan: Membangun Kesadaran Ekologis untuk Masa Depan Berkelanjutan - Rachman, Budhy Munawar (MAARIF, 2024)
This article explores the relationship between religion and ecology in addressing the urgency of the global environmental crisis. A reflective and analytical approach demonstrates that religious values, such as moral and spiritual responsibility towards nature, can play a crucial role in enhancing ecological awareness and motivating collective sustainable actions. Based on a review of various religious values and traditions, the article identifies three key findings: (1) religious teachings can strengthen intergenerational responsibility in environmental preservation; (2) integrating religious values with ecological principles creates a more effective holistic approach to mitigating environmental crises, and (3) interfaith and interdisciplinary collaboration catalyzes significant social change. The article’s contribution lies in expanding the academic discourse on ecology by highlighting spirituality’s role as a vital component of sustainability strategies. By combining religious and scientific perspectives, it offers a framework to address contemporary and future environmental challenges.